Use Of Slang Among Gen-Z - Kusyairi; Jamilatin Nisa; Rani Febrianti (Penerbit Hellow Pustaka, 2024)
As time progresses, many changes have occurred in the use of Indonesian in accordance with EBI. This especially happens among Gen-Z, who are currently finding it increasingly difficult to use Indonesian properly and correctly, for example by abbreviating words, adding letters to standard words, using letters, and using slang in everyday life. The large number of Indonesian people who use slang and abbreviations in their daily communication is a deviation from using Indonesian properly and correctly. This can hinder the growth and development of the Indonesian language. Lack of awareness to love and use Indonesian in one's own country will have an impact on the fading or disappearance of Indonesian in its use in society, especially among Gen-Z. Moreover, with the rise in the world of artists using slang in the mass and electronic media, Gen-Z people are increasingly imitating it in their daily lives. This is natural because Gen-Z people like to imitate new things.